Development of Innovative Leadership for School Administrators in Thailand 4.0 Era - Mrazek, Punniththa (Journal of Information and Learning [JIL], 2022)
School administrators in the Thailand 4.0 era are those who have been appointed to lead educational organizations, to secure, prosper and sustain as well as be able to cope with rapidly changing opportunities and threats. For people who will be leaders or administrators of schools, it is absolutely necessary to have skills, a vision to support or bring change, and creativity to build teamwork for providing opportunities to all sectors in order to share ideas, work together, appreciate their work, and to create an atmosphere of an innovative organization. Innovative leadership can manage the educational management system of schools. This will encourage all the staff to have their ideas, understanding and behavior to reflect on the innovative leadership. These will then lead to innovation to achieve the goal of creating value-added changes to educational institutions. The innovative leadership can use concepts, methods and technologies continuously to make academic institutes develop with quality. Therefore, for school administrators, it is necessary to have five skills, six leadership qualities, and four practice guidelines. The five skills are: associational thinking, observation of work, questioning for possibilities, networking with other people from different backgrounds, and experimentation for testing new ideas. The six qualities to demonstrate leadership are: developing right group norms, showing a team building strategy, showing interactions with people outside the team, showing support for leadership, showing school support, and showing effective management.